Extreme Velocity Fluctuations below Free Hydraulic Jumps - Raúl Antonio Lopardo (Journal of Engineering)
The internal flow of hydraulic jump is essentially an unsteady flow subjected to macroturbulent random fluctuations, and it was not known enough. Then, for the fluctuating motion interpretation, the experimental research on the associated turbulence must be necessary. The author developed in the past extensive laboratory research for the instantaneous pressure field determination by means of pressure transducers and new introductory experiments on velocity fluctuations by means of the ADV technique. The experimental study of the instantaneous pressure field was based on the knowledge of several statistical parameters of amplitudes and frequencies as functions of the Froude number, but for this paper the maximum instantaneous negative of pressure amplitudes on the floor is considered, in order to estimate the extreme maximum positive velocities near the bottom. A useful relationship between turbulence intensity and the pressure fluctuation coefficient was proposed from ADV velocity fluctuation for low incident Froude numbers. By means of this relationship, the value (instantaneous positive semiamplitude with 0.1% of probability to be surpassed) can be considered for the determination of the turbulent extreme velocity near the bottom, under a free hydraulic jump stilling basin with incident Froude number .